Experimental improvement of flyash as a growth medium for plants through addition of selected solid wastes - Webster, Glen Robert (Department of Geological Sciences, 2016)
Large quantities of coal are consumed in South Africa as a result of the generation of electricity and the manufacture of automotive fuel. A consequence of this was the production of more than 15 Mt of ash and associated coal combustion by-products in 1987 alone. This poses a large scale waste-disposal problem. Flyash, the major waste product is from South African coal sources, an alkaline, saline material the pozzolanic nature of which results in the formation of massive, compacted and cemented ash deposits which have significant environmental impacts. Efforts made to limit this impact by revegetation, in many locations throughout the world, have had limited success due to the mobility of phytotoxic concentrations of some elements, including As, B, Cr, Cu, Mo, Ni, S and Se. Flyash also has limited quantities of bioavailable Fe, Mn, P and Zn and these elemental limitations are associated with the alkaline nature of the flyash. Another element that is deficient, is N, it is unavailable in flyash as it is lost from coal during combustion. Aside from the chemical limitations to plant growth, the compacted nature results in low porosity which can limit plant available moisture. Plant root penetration is also impeded which limits nutrient uptake. The basis of this study was to incorporate other selected waste materials into the flyash to produce, by co-disposal, a combined waste material that is geochemically inert and a satisfactory plant growth medium. The ameliorants selected for inclusion in this study included interphase sulphur, a Vcontaminated waste sulphur product from the sulphur recovery plant at the SASOL' s Secunda petrochemical production facility and Catpoly, a spent catalyst consisting of phosphoric acidimpregnated diatomaceous earth, also obtained from SASOL's Secunda operation.